Structure of the Solar Atmosphere: A Radio Perspective - Alissandrakis, Costas E. (Frontiers in Astronomy and Space Sciences, 2020)
Solar radio emission has been providing information about the Sun for over half a century. In order to fully exploit this information, one needs to have a broader view of the solar atmosphere, which cannot be provided by radio observations alone. The purpose of this review is to present this background information, which is necessary to understand the physical processes that determine the solar radio emission and to link the radio domain with the rest of the electromagnetic spectrum.